Self-reported low back pain intensity and interferences among three-wheel drivers in Southwest of Ethiopia: A Community-Based Cross-sectional Study - Kebede, Ebissa Bayana; Terfa, Yonas Biratu; Tucho, Abdisa Eba; Germossa, Gugsa Nemera; Hailu, Fikadu Balcha; Abdisa, Birhanu; Mamo, Selam Ayele; Enbakom, Mestawet Getachew; Akuma, Adugna Olani (International Journal of Occupational Safety and Health, 2023)
Introduction: Low back pain is one of the most reported conditions among vehicle drivers. However, there is a paucity of information about low back pain experiences among three-wheel drivers in Ethiopia. This study aimed to determine the low back pain experience among three-wheel drivers in Ethiopia Jimma City, Southwest Ethiopia. Methods: A Community-based cross-sectional study was conducted from March 1-25, 2020 among 396 samples. Computer generated simple random sampling method was employed to get the required sample. An interviewer-administered questionnaire was used to collect the data. The data was checked for completeness, coded, cleaned and entered into Epi-data version 3.1 and exported to SPSS version 23 for analysis. Data was analyzed using mean and standard deviations for continuous and proportions for categorical variables. Binary and multivariable logistic regression was used to see an association between dependent and independent variables. P-value <0.05 at 95% CI was declared statistically significant. Results: Of 396 study participants, 26.26% of them had low back pain at any time among which, 73.1% reported pain in the last 24 hours. Regarding pain intensity in 24 hours, the mean ± standard deviation of worst pain was 5.3 ± 2.5. The independent variables significantly associated with low back pain along with their adjusted odds ratio (95% confidence interval) were: age 3.45 (1.98, 6.03), educational status: 1.96 (1.07, 3.59), physical exercise: 0.52 (0.31, 0.86) drinking alcohol: 2.32 (1.22, 4.39) and working hours: 0.32 (0.13, 0.83). Conclusion: The three-wheel drivers experienced moderate to severe low back pain and moderate to severe functional and emotional interferences. More than half of the participants reported the worst pain experience within 24 hours. Age, educational status, physical exercise, drinking alcohol and working hours were significantly associated with low back pain.